Representação de identidades e estereótipos nos espaços arquitetônicos em telenovelas brasileiras - Rossete Junior, Everton Nazareth (2024)
The effects of the content presented in mass media, mainly through television and the internet, on everyday life are widely perceived and experienced by a large part of the population. In this context, this thesis sought to identify in what ways and with what intensity architectural representations in Brazilian soap opera scenes reproduce and influence the construction and representation of the perception of identities and stereotypes. In an interdisciplinary way, the theoretical basis of this research studies architectonic spaces, basing on concepts relating to contemporary culture and communication. Observing the influence of architecture on everyday life, the focus of the research was mainly on residential interiors - through the study of the living room -, paying attention to the elements that characterize the homes of certain social groups within a dramaturgical plot. A methodological approach involving Content Analysis, Image Analysis and Discourse Analysis was used, with the selection of case study objects - the Brazilian soap operas Senhora do Destino, Avenida Brasil and Amor de Mãe. Thus, we confirmed the hypothesis that the architectural conformation represented in soap opera scenarios acts as a source of construction and perpetuation of social, economic and cultural identities, through stereotypes and values implicitly transmitted in the narrative and visual representations.